A review on quality management system and artificial intelligence methodology in autonomous vehicle development - Wang, Hao; Asrul, Adam; Yang, Wenbo (IOP Publishing, 2020)
Quality management is important for autonomous vehicles because the software and hardware in autonomous vehicles are more complicated than conventional vehicles. The potential risks arise due to it is difficult to identify them in the early stage in the product development process. Researchers are lack of quality management knowledge and with limited resource and information to develop the autonomous vehicle. Different quality management systems and standards related with autonomous vehicle are introduced and compared in this study. This study presents a simplified product development process that integrate the process method, failure mode, and effect analysis methods. This study also introduces a review of artificial intelligence approach into this process.